Consumer confidence and stock markets 'returns - Gaspar, Raquel M. (2023)
This study provides new insights on the relationship between changes in consumer con dence indices worldwide and the performance of European, United States and Chinese stock markets, during the period from 2007 to 2021. We look both into global and industry returns. For the full-time period, we nd stock market returns tend to be positively correlated with changes in consumer con dence indices, with signi cant two-way Granger causal impacts between the two variables for Europe and the United States. For the Chinese stock market we nd less pronounced and only one-way impact { changes in consumer con dence indices can Granger explain Chinese stock returns, but not vice versa. In fact, Chinese stock returns only help explaining changes in East Asian consumer con dence index. These results are robust across industries. For the Covid pandemic sub-period, we nd some negative correlations between stock market returns and changes in consumer con dence indices. This is particularly evident in China, but it also happens in Europe and United States, at least for some industries, including Health Care. Overall, the connection between the stock market performance and changes in consumer con dence is lower for USA and European stock markets, but it is higher for the Chinese stock market, in terms of the number of signi cant outcomes.